1993
DOI: 10.1243/pime_proc_1993_207_021_02
|View full text |Cite
|
Sign up to set email alerts
|

Design and Performance of a High-Pressure Ratio Turbocharger Compressor Part 2: Experimental Performance

Abstract: The performance of two turbocharger impeller designs was evaluated experimentally. The compressor design requirement was for a pressure ratio of 3.6, with a peak pressure ratio of 4.3 at a maximum non-dimensional impeller speed of 1.66. Due to the stress-limited speed the impeller discharge blade backsweep had to be restricted and the application of prewhirl was considered from the outset as a means of extending the operating range. An impeller, designated A, was designed with 25° of prewhirl applied. A second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
2
1
Order By: Relevance
“…One interesting conclusion they pointed out during their studies is the negative pre-whirl setting had higher potential to increase the surge margin than the positive pre-whirl setting. This conclusion is in contrast to the previous studies [281,282,305,355,356,357,360,363] where it was demonstrated the surge limit is improved when the pre-whirl has the same direction as the compressor wheel. To explain this different behavior, the authors paid special attention to the flow distribution imposed by the radial inlet and centripetal vanes of the swirl generator, with low velocities at the center and high velocities at the periphery of the compressor inducer.…”
Section: Pre-whirl Generatorscontrasting
confidence: 99%
See 1 more Smart Citation
“…One interesting conclusion they pointed out during their studies is the negative pre-whirl setting had higher potential to increase the surge margin than the positive pre-whirl setting. This conclusion is in contrast to the previous studies [281,282,305,355,356,357,360,363] where it was demonstrated the surge limit is improved when the pre-whirl has the same direction as the compressor wheel. To explain this different behavior, the authors paid special attention to the flow distribution imposed by the radial inlet and centripetal vanes of the swirl generator, with low velocities at the center and high velocities at the periphery of the compressor inducer.…”
Section: Pre-whirl Generatorscontrasting
confidence: 99%
“…With compressor wheel optimization in mind, Whitefield et al [356,357] manufactured in 1993 a special impeller to take full advantage of a positive prewhirl of 25 ¥ . The impeller backsweep was only 7 ¥ and the inducer blade angle at the tip was selected as -50 ¥ to correspond with the minimum relative Mach number.…”
Section: Pre-whirl Generatorsmentioning
confidence: 99%
“…However, when the diesel engine is operated under a low-power condition, the compressor loses the ability to provide adequate air supply with proper pressure for the diesel engine [6]. To solve this problem, the variable-geometry compressor (VGC [7][8][9][10], including a variable inlet guide vane [11][12][13] and variable-geometry diffuser [14][15][16]), is introduced into the turbocharger in the diesel engine. With the VGC, the operation range and the efficiency of compressor are expanded extensively, particularly under low mass flow rate and high pressure ratio conditions [17].…”
Section: Introductionmentioning
confidence: 99%